RECOGNIZABILITY OF SOME NON-WOOD FOREST PRODUCTS BY YOUNG PEOPLE: CASE OF ATABEY VOCATIONAL SCHOOL, ISPARTA, TURKEY - Sarıkaya, Ayşe Gül (Health & Environment Assoc, 2019)
Survey was conducted with 150 person who are students 1st and 2nd grades in three departments of Applied Sciences University of Isparta, Atabey Vocational School: Computer Technologies, Office Management and Secretary and Forestry. The survey consists of 2 sections according to the demographic characteristics, the identification of 25 plants and their intended use status. The data of the study were analyzed by transferring the data into SPSS 22.0 statistics program. The chi-square test was used to determine the students' perception of plants with respect to gender and department of education p <0,05. None-wood forest products, the students who participated in the survey recognized the most were determined to be; walnut (99.3%), almond (98%), linden (98%), sage (97.3%) and chestnut (97.3%). It was determined that the students recognized haw (44%), balm (36.7%) and saffron (24%) plants the least. There was a significant difference with respect to gender in status of recognition non-wood forest products for balm, fennel and sweetgum plants. There was a significant difference with respect to department of education in status of recognition non-wood forest products for haw, blackberry, chestnut, mint, balm, fennel, sweetgum and sumac.
Keywords: Non wood forest product; Atabey Vocational School; survey; student